2011
DOI: 10.1002/ijc.25847
|View full text |Cite
|
Sign up to set email alerts
|

Sessile serrated adenomas and classical adenomas: An epigenetic perspective on premalignant neoplastic lesions of the gastrointestinal tract

Abstract: The diagnosis of sessile serrated adenomas (SSAs) is challenging, and there is a great deal of interobserver variability amongst pathologists in differentiating SSAs from hyperplastic polyps (HPPs). The aim of this study was (i) to assess the utility of epigenetic changes such as DNA methylation in differentiating SSAs from HPPs and (ii) to identify common methylation based molecular markers potentially useful for early detection of premalignant neoplastic lesions of gastrointestinal tract. A total of 97 prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 47 publications
3
49
0
Order By: Relevance
“…13,14,22,25,26 In previous reports, 18-100% of adenomas and 78% of adenocarcinomas of the colorectum displayed nuclear b-catenin immunoreactivity. 14,22,25 Various investigators have reported that nuclear b-catenin expression was observed in 0-60% of SSA/Ps, 7,9,13,14,22,25,26 43-100% of SSA/Ps with high-grade dysplasia, 9,13,14 and 60% of SSA/Ps with submucosal carcinoma. 13 Nuclear b-catenin labeling indices in our study were significantly lower in the SSA/P series than the adenoma series, suggesting that levels of WNT/b-catenin signaling activation may be different between the serrated neoplasia pathway and the conventional adenoma-carcinoma sequence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13,14,22,25,26 In previous reports, 18-100% of adenomas and 78% of adenocarcinomas of the colorectum displayed nuclear b-catenin immunoreactivity. 14,22,25 Various investigators have reported that nuclear b-catenin expression was observed in 0-60% of SSA/Ps, 7,9,13,14,22,25,26 43-100% of SSA/Ps with high-grade dysplasia, 9,13,14 and 60% of SSA/Ps with submucosal carcinoma. 13 Nuclear b-catenin labeling indices in our study were significantly lower in the SSA/P series than the adenoma series, suggesting that levels of WNT/b-catenin signaling activation may be different between the serrated neoplasia pathway and the conventional adenoma-carcinoma sequence.…”
Section: Discussionmentioning
confidence: 99%
“…9 SFRP1 and 2 were earlier reported to be methylated in 90-100% of SSA/Ps and those with dysplasia 9 as well as in 80-90% of conventional tubular adenomas and adenocarcinomas. 19 By contrast, SFRP4 was highly methylated in SSA/Ps (85%) and those with high-grade dysplasia (83%), 9 whereas its methylation was relatively low in conventional adenomas (24%) and adenocarcinomas (36%). 19 We also confirmed that SFRP1, 2, and 4 were methylated in most (82-100%) of the SSA/P series, but figures for SFRP4 were relatively low (37-50%) in the adenoma series.…”
Section: Modern Pathology (2015) 28 146-158mentioning
confidence: 98%
See 2 more Smart Citations
“…[24][25][26] In CRC, CIMP positivity (CIMP+) has been associated with older age, female sex, proximal colon lesions, mucinous tumors, poor differentiation, microsatellite instability and BRAF mutations. 15,27,28 In serrated and adenomatous colorectal polyps, CIMP+ correlates with large size, right-sided location, and amount of villous component within the adenomas. 16 CIMP+ has also been described in small bowel carcinomas including those of the duodenum.…”
Section: Introductionmentioning
confidence: 99%